Cooperative Intrasectoral Specialization as A Regional Growth Strategy in Northeast Asia (Mongolian Journal of International Affairs, 2015)
No abstract available. DOI: http://dx.doi.org/10.5564/mjia.v4i0.418 Mongolian Journal of International Affairs Vol.4 2007: 35-47